Recent advances in the pathogenesis and treatment of kidney disease - Nitta, Kosaku (Contributions to nephrology / series editor Claudio Ronco, 2018)
Chronic kidney disease (CKD) is a global health burden with associated high economic costs to the health system. Main factors are the increasing number of patients with diabetes and hypertension and the aging of the population. CKD has been associated with increased risks of cardiovascular morbidity, premature mortality, and/or decreased quality of life. In this new volume, renowned Japanese scientists present their recent research results. Papers cover various aspects of kidney diseases such as cystic kidney diseases, treatment of lupus nephritis, renal anemia and iron metabolism, cell sheet engineering, frailty and outcomes of dialysis patients, and the socioeconomics of rituximab in nephrotic syndrome. Due to the wide range of topics presented, this book will be of interest to readers from various clinical and research settings connected with the care of CKD patients.